FORMULASI ETIKA SOSIAL TERHADAP SESAMA MANUSIA DALAM SURAH AL- ḤUJURĀT: PENDEKATAN TEMATIK - Hayyin Mazaya Nisa'; Moh. Alwy Amru Ghozali (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
Using Nurcholish Madjid’s functional-sociological approach, this study aims to explore and formulate the values of social ethics contained in Surah al-Ḥujurāt through a thematic exegesis framework (tafsīr mawḍūʿī). This surah encompasses fundamental teachings on community ethics, such as respect toward authority, the principle of caution in receiving information (tabayyūn), the obligation to reconcile conflicts (iṣlāḥ), and prohibitions against mockery, prejudice, and backbiting. Employing a qualitative method with a library research approach, the study analyzes classical and contemporary tafsīr sources using descriptive-analytical techniques. The findings reveal that the social values in Surah al-Ḥujurāt are universal, contextual, and applicable. The verses construct a comprehensive system of Islamic social ethics, ranging from epistemic foundations (verses 1–2), digital information ethics (verse 6), conflict management (verses 9–10), interpersonal communication ethics (verses 11–12), to principles of inclusivity and equality (verse 13). This surah serves as both a normative and practical reference for character development and the cultivation of a dignified, ethical, and harmonious society